DEVELOPMENT OF QUARTET CARD LEARNING MEDIA ON SOLAR SYSTEM MATERIAL - Uswatun, Siti Uswatun; Oktaffi Arinna Manasikana (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2023)
This development research is conducted to help learners understand new terms in solar system materials. The characteristics of the material that give rise to many new terms require learners to remember these terms. For that, a fun way is needed to help students understand the material. The objectives of this study are: 1) describe the process of developing quartet card media as a class VII learning media. 2) describe the feasibility of quartet card teaching media on solar system material in junior high school grade VII based on validity, practicality and effectiveness The results of research on the development of science quartet card learning media on solar system materials showed that media validity received an average score of 3.66 for the very valid category and 3.75 for the